Die Wirkung des Kündigungsschutzes auf die Stabilität "junger" Beschäftigungsverhältnisse - Bernhard Boockmann; Daniel Gutknecht; Susanne Steffes (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– In the past few years numerous studies have dealt with the employment effects of Germany's dismissal protection legislation. The majority of the studies, however, found no significant effects on aggregate exit and entry rates in the firms affected. In our analysis we estimate the effect of dismissal protection on the individual job stability of newly created employment relationships. For the study we use the change in the threshold value for the applicability of dismissal protection, which came into effect in 1999, as a natural experiment. Our findings point to a positive effect of dismissal protection on the stability of newly created employment relationships. However, this effect only emerges after approximately 200 days, which corresponds to the waiting period before dismissal protection comes into effect.
Keywords: 330; Kündigungsschutz - Auswirkungen; Beschäftigungseffekte; Arbeitsplatzsicherheit; IAB-Linked-Employer-Employee-Datensatz